Bus cache-based location privacy protection scheme in the Internet of vehicles - Jie CUI; Xuefeng CHEN; Jing ZHANG; Lu WEI; Hong ZHONG (Tongxin xuebao)
To solve the problem of real location leakage when vehicles use location-based service (LBS) on the Internet of vehicles, a location privacy protection scheme based on bus cache was proposed.Firstly, a point of interest (POI) pool was obtained from the LBS provider based on its route information.Then the data in the POI pool was selected form a POI list while driving.Finally, the POI list was broadcast to surrounding private vehicles.After the private vehicle received the broadcast data, it verified the identity of the bus and then stored the POI list in the vehicle’s local cache.When a private vehicle needed to query POI information, it would first retrieve it in the local cache, and if the cache was missed, it would send a query request to the LBS provider using the k-anonymity method.The simulation experiment results show that the proposed scheme can reduce the possibility of leakage of the real location of the private vehicle by reducing the number of communications between the private vehicle and the LBSP, thereby effectively improving the privacy protection level of the private vehicle.